1992
DOI: 10.1620/tjem.168.97
|View full text |Cite
|
Sign up to set email alerts
|

Specific Expression of Glutathione S-transferase Pi Forms in (Pre)neoplastic Tissues: Their Properties and Functions.

Abstract: The detection of preneoplastic cells is very important for the analysis of carcinogenic processes and for developing strategies for prevention and treatment of cancer. We have been investigating enzyme alterations occurring during rat chemical hepatocarcinogenesis, especially to find more specific enzyme markers for preneoplastic hepatic lesions. We identified the placental form of glutathione S-transferese (GST-P ; GST 7-7) as a new marker enzyme for preneoplastic hepatocytes. We also found human placental fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…GSTP1-1 is overexpressed in various cancers, including gastric cancer, lung cancer, ovarian cancer, and precancerous lesions 35–38 . Therefore, our data suggest that a fluorogenic probe targeting GSTP1-1 for molecular imaging would also be very useful for the early diagnosis and/or evaluation of chemopreventive agents for these types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…GSTP1-1 is overexpressed in various cancers, including gastric cancer, lung cancer, ovarian cancer, and precancerous lesions 35–38 . Therefore, our data suggest that a fluorogenic probe targeting GSTP1-1 for molecular imaging would also be very useful for the early diagnosis and/or evaluation of chemopreventive agents for these types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…1), we found that the induction of γ-H2AX was reduced when the intracellular levels of glutathione were depleted by BSO. Together the above results further justify the rationale for using brostallicin in tumors with high glutathione levels, which is a relatively common feature of cancer cells especially after prior chemotherapy (7, 18–20, 2325, 44). …”
Section: Discussionmentioning
confidence: 54%
“…Indeed, the DNA damaging activity of brostallicin is enhanced by high levels of glutathione, which is a hallmark of drug-resistant tumor cells (7, 18, 2125). We also show for the first time that brostallicin selectively damages and blocks replicating DNA within replication factories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that abnormal tumor suppressor gene promoter methylation could inactivate the corresponding genes and thus promote tumor development and progression (7,8). The GSTP1 gene is a very important DNA damage repair gene that can inhibit the effects of cytotoxic agents and carcinogens and is regarded as a tumor suppressor gene (9). Previous studies have also demonstrated that hypermethylation of the CpG islands in the GSTP1 gene promoter is involved in the development and progression of multiple tumors, and thus could be used as a promising biomarker to help early screening, diagnosis, and patient prognosis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%